Richard Clogg, Antolica. Studies in the Greek East in the 18th and 19th centuries - Ανεστίδης, Σταύρος Θ. (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1997)
[ Δε διατίθεται περίληψη / no abstract available]